Learning and competences of management students in Brazil: the participation of organizations and university in process of supervised internship - Souza Júnior, Roberto Rodrigues de; Dumer, Miguel Carlos Ramos; Cerqueira, Alexandre dos Santos; Mendonça, Mark Miranda de; Azevedo, Filipe Bressanelli (Archives of Business Research, 2018)
The main objective of this study is to describe and analyze the contribution of universities and businesses in the learning and development of professional skills of supervised students in the Administration of the Federal University of Espírito Santo (Brazil). The main approaches that anchor the present study focus on the individual actions that generates learning and consequently the development of competencies. Thus, the concepts of competency learning through social, experiential and education-based approaches to build competencies and resources mobilization. The present qualitative research approach used the interpretative paradigm. We applied the technique of in-depth interview for the data collection, and for the discussion of the results, we used the qualitative data analysis. As a result, we found the need for a new look at the supervised internship discipline both by the organizations and the University. Additionally, we found the need to create an environment that allows greater interaction between the actors directly involved, providing new tools to follow the discipline with greater control by coordinators and internship process norms. All these results can make possible the integration of content and practice in an effective way.